Epidemiological Features of COVID-19 in Makkah City: A Retrospective Data Analysis. (24th February 2022) - Asghar, Atif; Bamaga, Majid; Khogeer, Asim; El-Rahim, Ibrahim Abd; Mashat, Bassam; Assaggaf, Hamza; Ahmed, Omar
Abstract : Background . Coronavirus disease 2019 (COVID-19) is continuing to circulate and change, affecting billions of people worldwide and leading to increased mortality rates, especially in the Holy City of Makkah, Kingdom of Saudi Arabia (KSA). This study was aimed at investigating the epidemiological features of COVID-19 in Makkah City, KSA. Methods . A retrospective analysis was conducted to investigate the prevalence of COVID-19 and the association between the severity and mortality of COVID-19 with demographic factors and comorbidities. Results . Among 4, 742 COVID-19 patients, the incidence rate observed in males was 66.7%, and 69.7% were from Al-Noor Specialized Hospital. The highest incidence rate (25.2%) was found in the age group > 60 years old, followed by the age group 51-60 years (21.8%). Furthermore, the highest frequency was observed in patients from Saudi Arabia (36.8%), followed by patients from Myanmar (14.7%) and Bangladesh (9.4%). The overall frequency of COVID-19 severity and death was 20.3% and 11.6%, respectively. Body mass index analysis showed that 1% of the patients were underweight, while 9.2% were overweight and 4.4% were obese. In addition, 9.6% had diabetes, 6.9% had hypertension, 1.1% had heart disease, and 2.2% had other chronic diseases. Conclusion . The study concluded that the overall percentages of severe COVID-19 (intensive care unit) cases and deaths in Makkah City, KSA, were 20.3% and 11.6%, respectively, and there was a higher incidence in male patients. The severity of infection was shown to have a strong significant correlation with different chronic diseases, nationality, body mass index, death rate (mortality), heart disease, and length of hospital stay (P < 0.05 ). Despite these findings, more studies are needed to explain the underlying mechanisms that influence the overall health status of patients with specific characteristics and comorbidities.